Pembinaan Organisasi , Administrasi, dan Keuangan Pengadilan Pajak Pasca Terbitnya Putusan Mk Nomor: 26/Puu-Xxi/2023 Terhadap Kekuasaan Kehakiman yang Merdeka - Taufiqurrahman, Fadhlan (UNES Law Review, 2023)
Tax court is one way to obtain justice in tax disputes in Indonesia. Prior to the decision of Indonesian Constitutional Court Number: 26/PUU-XXI/2023, the authority to supervise tax court was divided into two separate institutions. Where Supreme Court of Indonesia has the authority over technical development and Ministry of Finance has the authority over organizational, administrative, and financial development of tax court in Indonesia. The division of authority over management of the tax court creates a tendency for dualism in term of development of the tax court. However, with the decision of Indonesian Constitutional Court Number: 26/PUU-XXI/2023 the supervisory authority for tax court is fully transferred to the Supreme Court. This can be a solution to the problem of dualism in the authority of the tax court. The impact of this transfer of authority on the judicial power of the tax court will be the topic of discussion discussed in this paper.